On the Determinants of Net Foreign Investment: Discussion - de Macedo, Jorge Braga (Journal of Finance, 1983)
Jorge Braga de Macedo, On the Determinants of Net Foreign Investment: Discussion, The Journal of Finance, Vol. 38, No. 2, Papers and Proceedings Forty-First Annual Meeting American Finance Association New York, N.Y. December 28-30, 1982 (May, 1983), pp. 472-475